Serum tumour necrosis factor‐α and interleukin‐6 levels in Alzheimer's disease and mild cognitive impairment - Kim, Yo Sup; Lee, Kang Joon; Kim, Hyun (Psychogeriatrics, 2017)
Background Neuroinflammation has been recognized as a feature of Alzheimer's disease (AD), and mild cognitive impairment (MCI) is believed to share several pathological features with AD. The aim of the present study was to compare serum cytokine levels between patients with AD, subjects with MCI, and healthy controls, and to assess the correlation between cytokine levels and cognitive performance in these subjects. Methods Participants included 35 patients with AD, 29 subjects with MCI, and 28 healthy controls from the Department of Psychiatry of IIlsan Paik Hospital in South Korea. Demographic and neuropsychological information were obtained, and peripheral cytokine levels, specifically tumour necrosis factor (TNF)‐α and interleukin (IL)‐6 levels, were measured for all subjects. Results After adjustment for age, a significant difference in IL‐6 levels (P = 0.045), but not in TNF‐α (P = 0.082) levels, was observed among the three groups. IL‐6 levels were higher in patients with AD than in subjects with MCI and healthy controls. TNF‐α and IL‐6 levels negatively and positively correlated with Mini‐Mental State Examination and Global Deterioration Scale scores, respectively. TNF‐α and IL‐6 levels were also positively correlated with each other. Conclusions The present study suggests that serum IL‐6 levels of patients with AD might be higher than those of subjects with MCI and healthy controls. Serum TNF‐α and IL‐6 levels might be negatively correlated with cognitive function, and we suspect that serum IL‐6 levels could be biomarkers for AD.